Effect of Import Tariffs on Indonesia-Australia Wheat Flour Prices and CIF Prices - Cici Solikha; Maswadi; Josua Parulian Hutajulu3 (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2021)
Import tariff of Indonesian-Australian wheat flour has been changed from 4% to 0% have implications for wheat flour prices in both countries. This research aims to determine the import tariffs effect on the price of Indonesian-Australian wheat flour and the CIF price of wheat flour. Descriptive quantitative is applied in this research method, with the approach of Vector Error Correction Model (VECM) and Granger Causality Test. The Granger Causality Test results analysis showed that there is a unidirectional causality relationship between HEI with HEA, HEA with KURS, TARIF with HEA, and TARIF with KURS. VECM’s results showed the import tariffs had a significant positive effect of the Indonesian-Australian wheat flour price and the CIF price in the long run. The Impulse Response Function (IRF) results analysis for the next 20 periods show that the highest responses given by HCIF, HEA, HEI, and TARIF is responses by variable itself and the highest responses given by KURS is TARIF. The Variance Decomposition results analysis for the next 20 periods show that the largest contribution given to HCIF, HEA, HEI, and TARIF is the variable itself and the largest contribution given to KURS is TARIF.